2018
DOI: 10.1021/acs.iecr.7b03443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Doping Rare Earth Elements (Y, La, and Ce) on Catalytic Performances of CoMo/MgAlM for Water Gas Shift Reaction

Abstract: Rare earth element (La, Y, and Ce) modified MgAl-hydrotalcites of MgAlM were synthesized from coprecipitation and calcination, and further loaded with CoMo active species to give CoMo/MgAlM catalysts. X-ray powder diffraction, inductively coupled plasma, and N2 adsorption isotherms indicate that MgAlM possess large BET surface areas (58–91 m2/g), and rare earth elements were successfully introduced into samples. CO2-TPD (temperature-programmed desorption), NH3-TPD, H2-TPR (temperature-programmed reduction), H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…The outcomes are peaks at 229.5, 230.3, and 233.5 eV binding energy attributable to Mo 3d 3/2 signals of MoS 2 species (Mo 4+ ), oxysulfide MoO x S y compounds (Mo 5+ ), and MoO 3 species (Mo 6+ ), respectively. As for the corresponding Mo 3d 3/2 signals, they appear at 232.6, 233.6, and 236.5 eV, showing a doublet separation of around 3.3 eV. , The relative contents of MoS 2 , MoO x S y , and MoO 3 species are listed in Table . Among the three catalysts, 2EAPA-Mo has the lowest percentage of MoS 2 species (57.4%) and the highest percentage of MoO x S y species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes are peaks at 229.5, 230.3, and 233.5 eV binding energy attributable to Mo 3d 3/2 signals of MoS 2 species (Mo 4+ ), oxysulfide MoO x S y compounds (Mo 5+ ), and MoO 3 species (Mo 6+ ), respectively. As for the corresponding Mo 3d 3/2 signals, they appear at 232.6, 233.6, and 236.5 eV, showing a doublet separation of around 3.3 eV. , The relative contents of MoS 2 , MoO x S y , and MoO 3 species are listed in Table . Among the three catalysts, 2EAPA-Mo has the lowest percentage of MoS 2 species (57.4%) and the highest percentage of MoO x S y species.…”
Section: Resultsmentioning
confidence: 99%
“…As for the corresponding Mo 3d 3/2 signals, they appear at 232.6, 233.6, and 236.5 eV, showing a doublet separation of around 3.3 eV. 40,41 The relative contents of MoS 2 , MoO x S y , and MoO 3 species are listed in Table 3. Among the three catalysts, 2EAPA-Mo has the lowest percentage of MoS 2 species (57.4%) and the highest percentage of MoO x S y species.…”
Section: Sulfidation Of Catalyst Precursorsmentioning
confidence: 99%
“…As a commercial catalyst, Cr/Al 2 O 3 has been widely used in dehydrogenation plants, (e.g., PDH), because of its high activity and selectivity for the reaction and its good mechanical stability. From the prospect of further applications, appreciable improvement in catalytic performance of this catalyst is of importance. Different promoters, such as transition-metal oxides (e.g., Ni, Co, Cu), are generally employed to enhance catalytic performance of Cr/Al 2 O 3 because positive changes of the structure and physicochemical properties of the support are achieved with the addition of suitable promoters. It has been reported that rare earth oxide ceria by Ce modification can increase catalytic performance of the supported catalysts by interacting with the support and/or increasing the dispersibility of the active metal component. , In fact, Ce was used as the promoter on the Cr-based catalysts for oxidative dehydrogenation of alkanes (e.g., isobutane, propane, and ethylbenzene) because of its excellent oxygen storage capacity, which can enhance the reduction–oxidation cycle between Cr 6+ and Cr 3+ species, thereby increasing the activity of the catalyst. However, investigations of the interaction between Ce and Cr species, and the effects of Ce modification on the dispersion and distribution of the active Cr phase have seldom been concerned in these works, especially for propane nonoxidative dehydrogenation (PDH) reaction. From this point of view, using CeO 2 to modify Cr/Al 2 O 3 for PDH arouses our interest in the present research.…”
Section: Introductionmentioning
confidence: 99%
“…16−18 It has been reported that rare earth oxide ceria by Ce modification can increase catalytic performance of the supported catalysts by interacting with the support and/or increasing the dispersibility of the active metal component. 19,20 In fact, Ce was used as the promoter on the Cr-based catalysts for oxidative dehydrogenation of alkanes (e.g., isobutane, propane, and ethylbenzene) because of its excellent oxygen storage capacity, which can enhance the reduction−oxidation cycle between Cr 6+ and Cr 3+ species, thereby increasing the activity of the catalyst. 21−26 However, investigations of the interaction between Ce and Cr species, and the effects of Ce modification on the dispersion and distribution of the active Cr phase have seldom been concerned in these works, especially for propane nonoxidative dehydrogenation (PDH) reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth oxides could improve the catalytic activity, dispersion, and stability of catalytic materials . In addition, the doping of rare earth oxides could increase the amount of basic sites of the catalysts . There have been some rare earth metal oxides used in biodiesel transesterification reactions, so it is meaningful to study the rare earth‐doped catalysts for glycerol transesterification.…”
Section: Introductionmentioning
confidence: 99%